Development of an Online Directory of CSU Ph. D. Awarded Thesis Portal for Central Sanskrit University Scholars Using Google Apps Script (LIS TODAY, 2025)
The Online Directory of CSU Ph. D. Awarded Thesis Portal is developed to address  the lack of a centralized mechanism for accessing thesis-related information at  Central Sanskrit University (CSU). Prior to this initiative, research scholars faced  many challenges in locating thesis topics, supervisors, subjects, year and the  availability of physical copies due to the absence of a searchable database. Existing  resources, such as non-searchable PDF lists of theses awarded from 2018 onward,  were inadequate, leaving earlier data inaccessible to the research scholars. This research highpoints the implementation of a dynamic web-based search  portal designed to provide real-time access to a comprehensive thesis database.  The portal integrates HTML and SQL-based technologies to facilitate efficient  retrieval of information such as thesis titles, authors, supervisors, and campus  locations of physical copies. Key features include user-friendly search functionality,  advanced filtering options, and automated database updates to ensure accuracy  and accessibility. The results demonstrate that the portal significantly enhances usability, reduces  inefficiencies, and supports scholars in identifying research gaps and opportunities  for further study. By bridging the accessibility gap and modernizing thesis data  management across CSU’s 12 campuses, the portal sets a new standard for resource  availability in academic institutions. This initiative underscores the importance  of leveraging digital tools to advance research and improve academic support  systems.
Keywords: Thesis Portal; Google Apps Script; Web App; Central Sanskrit University; Online Directory